Pengaruh Edukasi pada Ibu-Ibu yang Mempunyai Anak Balita melalui Pelatihan Pengolahan Nugget sebagai Sumber Protein di Desa Tanjung Garbus : Pengabdian - Tiar Lince Bakara; Rumida; S Nainggolan, Efendi; Sitanggang, Berlin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
To support stunting prevention efforts, a Community Service Program (PKM) was implemented under the title “The Effect of Nutrition Education on Mothers with Toddlers through Training on Nugget Processing as a Protein Source in Tanjung Garbus Village, Lubuk Pakam District, Deli Serdang Regency.” The program aimed to enhance mothers’ knowledge and skills in utilizing local food ingredients to produce nutritious, protein-rich products. The activity was conducted over two months using several stages: pre-test, education, training (cooking demonstration), post-test, and skill evaluation. Education sessions were delivered through lectures, discussions, and hands-on practice, involving 20 active participants. The results indicated an improvement in participants’ knowledge, with the average pre-test score increasing from 12.85 to 12.90 and the proportion of participants categorized as having “good” knowledge rising from 15% to 85%. Although attitudes toward nutritious food consumption showed a positive shift, the change was not statistically significant (p > 0.05), and behavioral practices remained relatively unchanged (p = 0.121). The nuggets produced during the training contained 9.33 g of protein and 144 kcal per 100 g, making them a viable alternative source of nutritious food for children. This program produced several outputs, including an educational booklet, activity video, and Intellectual Property Rights (IPR).